Restructuring and reform of Indian political, administrative and economic system - Dubhashi, P.R. (1997)
The author first makes an analytical presentation on the political, administrative and economic components of our system that we adopted 50 years ago, followed by a point-wise presentation on the malaise that has set in our system, and then, to remedy it gives a systemic reform agenda touching all the three components. - Reproduced
Keywords: Public administration - India; Public administration